Peran Kepela Sekolah dalam Meningkatkan Profesionalisme Guru di SMPN 3 Jerowaru - Ahmad Izzudin; M. Irwan Hadi; Dita Meitia (Pendidikan Al-Gafari, 2023)
The head school has a very important role in advancing the institution he leads. Quality something institution education depends on the head school as a leading institution. Then head the school's task to give guidance and supervision to every teacher on duty in the field of their respective studies. To operate his task as a builder and supervisor in developing teacher professionalism and improving quality effective learning, then a head school must own ability and understanding about competence of head school with Good. Study This aims: 1) Describe the role of head school in increasing teacher professionalism at SMPN 3 Jerowaru 2) Describe the level of teacher professionalism at SMPN 3 Jerowaru 3) Describe factors that just be supporting and inhibiting head school to increase teacher professionalism at SMPN 3 Jerowaru. Study This uses an approach qualitative. Data collection techniques were carried out through observation, interviews, and documentation. Whereas technique researcher data analysis uses method descriptive qualitative. From the results analysis can be known that the role of the head school in increasing teacher professionalism at SMPN 3 Jerowaru is done through several matters among them the head school role as an educator, manager, administrator, supervisor, and motivator. Whereas condition teacher professionalism at SMPN 3 Jerowaru spelled out enough good. The teacher has fulfilled sufficient qualifications, as always following various training and workshops. As for factors that support head schools in increasing teacher professionalism with exists factor support from the background behind good teacher education and coaching cooperation between teachers. Whereas factor inhibitor head school lacks means prasana, as well as the level of parental concern for participants' educates.